2019
DOI: 10.3390/ma12233878
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Fe3O4@SiO2–Pt and Fe3O4@SiO2–Pt@SiO2 Structures for HDN of Indole

Abstract: The effect of a second porous SiO2 shell in the activity and selectivity of the Fe3O4@SiO2–Pt catalyst in the hydrodenitrogenation of indole is reported. The double Fe3O4@SiO2–Pt@SiO2 structure was prepared by coating Fe3O4 nanoparticles with tetraethyl orthosilicate (TEOS) with a further impregnation of 1.0 wt.% of Pt on the (3-aminopropyl)triethoxysilane functionalized Fe3O4@SiO2 structures. The second porous SiO2 shell, obtained by using a hexadecyltrimethylammonium bromide (CTAB) template, covered the Fe3O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Although piperidine was not to be found in this experiment, most likely because conversion of piperidine happened quickly and piperidine was consumed completely within 5 min, the hydrogenation route from pyridine to piperidine was widely reported by other research studies. Therefore, we reasonably treat piperidine as an intermediate product in the model. Considering that hydrogenation of the nitrogen heterocyclic ring substance is a reversible reaction, dehydrogenation of piperidine is also included in this network (eqs and ). Piperidine disappearance is involved in the following reactions: 1-piperidineethanol formation via the reaction between piperidine and formic acid (eq ), generation of 1-carbaldehyde piperidine by substitution of H on the N atom in pyridine with formic acid (eq ), formation of other piperidines via the derivative reaction (eq ), and 1-pentanol formation after ring rupture of piperidine (eq ), which further combines with piperidine and leads to formation of 1-pentyl piperidine (eq ). Next, both 1-piperidineethanol and 1-carbaldehyde piperidine can further undergo hydrogenation to form 1-ethyl piperidine (eq ) and 1-methyl piperidine (eq ), respectively. Considering that the hydrogenolysis of short-chain amines, alcohols, and hydrocarbons could occur under supercritical water conditions, we lump those minor amines, alcohols, hydrocarbons, and gas products together as NH 2 -R, HO-R, C n H m , and GP, respectively, in the network.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although piperidine was not to be found in this experiment, most likely because conversion of piperidine happened quickly and piperidine was consumed completely within 5 min, the hydrogenation route from pyridine to piperidine was widely reported by other research studies. Therefore, we reasonably treat piperidine as an intermediate product in the model. Considering that hydrogenation of the nitrogen heterocyclic ring substance is a reversible reaction, dehydrogenation of piperidine is also included in this network (eqs and ). Piperidine disappearance is involved in the following reactions: 1-piperidineethanol formation via the reaction between piperidine and formic acid (eq ), generation of 1-carbaldehyde piperidine by substitution of H on the N atom in pyridine with formic acid (eq ), formation of other piperidines via the derivative reaction (eq ), and 1-pentanol formation after ring rupture of piperidine (eq ), which further combines with piperidine and leads to formation of 1-pentyl piperidine (eq ). Next, both 1-piperidineethanol and 1-carbaldehyde piperidine can further undergo hydrogenation to form 1-ethyl piperidine (eq ) and 1-methyl piperidine (eq ), respectively. Considering that the hydrogenolysis of short-chain amines, alcohols, and hydrocarbons could occur under supercritical water conditions, we lump those minor amines, alcohols, hydrocarbons, and gas products together as NH 2 -R, HO-R, C n H m , and GP, respectively, in the network.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, path 1r has a direct or an indirect strong impact on each compound, which suggests that dehydrogenation from piperidine to pyridine cannot be negligible. Indeed, for HDN of nitrogen heterocyclic ring chemicals such as indole, quinoline, carbazole, and so forth, dehydrogenation was an indispensable and essential step during the whole reactions. For pyridine, except for path 1 and path 1r, other paths have little impact on it.…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the combustion value of indole, it is necessary to convert indole into alkanes by denitrification and ring opening reactions. Based on prior works [18][19][20], noble metal catalysts, such as Pt, are good for hydrogenation reactions, while the catalysts with an acidity function, such as Ni, are good for ring opening reactions. As mentioned above, it has been reported that Pt and Ni experimentally presented high catalytic activity for indole hydrodenitrogenation.…”
Section: Introductionmentioning
confidence: 99%